State Categories, Bureaucracies of Displacement, and Possibilities from the Margins - Menjívar, Cecilia (American Sociological Review, 2023)
In this presidential address, I argue for the importance of state-created categories and classification systems that determine eligibility for tangible and intangible resources. Through classification systems based on rules and regulations that reflect powerful interests and ideologies, bureaucracies maintain entrenched inequality systems that include, exclude, and neglect. I propose adopting a critical perspective when using formalized categories in our work, which would acknowledge the constructed nature of those categories, their naturalization through everyday practices, and their misalignments with lived experiences. This lens can reveal the systemic structures that engender both enduring patterns of inequality and state classification systems, and reframe questions about the people the state sorts into the categories we use. I end with a brief discussion of the benefits that can accrue from expanding our theoretical repertoires by including knowledge produced in the Global South.